2003
DOI: 10.1152/jn.00226.2003
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D4 Receptor-Mediated Presynaptic Inhibition of GABAergic Transmission in the Rat Supraoptic Nucleus

Abstract: . Dopamine D4 receptor-mediated presynaptic inhibition of GABAergic transmission in the rat supraoptic nucleus. J Neurophysiol 90: 559 -565, 2003; 10.1152/jn.00226.2003. The mechanism by which dopamine induces or facilitates neurohypophysial hormone release is not completely understood. Because oxytocin-and vasopressin-secreting supraoptic neurons are under the control of a prominent GABAergic inhibition, we investigated the possibility that dopamine exerts its action by modulating GABA-mediated transmission. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 50 publications
2
21
0
2
Order By: Relevance
“…This is consistent with previous reports demonstrating a similar D 4 -mediated mechanism responsible for decreasing the release of both GABA (Azdad et al, 2003) and glutamate (Price and Pittman, 2001) at terminals in the SON. It is interesting that, although a specific agonist of the D 4 receptor inhibits both GABA and glutamate release, there is little effect of quinpirole, a nonselective agonist of the D 2 -like family (including D 4 ) of dopamine receptors in either the current study or previous work (Price and Pittman, 2001).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This is consistent with previous reports demonstrating a similar D 4 -mediated mechanism responsible for decreasing the release of both GABA (Azdad et al, 2003) and glutamate (Price and Pittman, 2001) at terminals in the SON. It is interesting that, although a specific agonist of the D 4 receptor inhibits both GABA and glutamate release, there is little effect of quinpirole, a nonselective agonist of the D 2 -like family (including D 4 ) of dopamine receptors in either the current study or previous work (Price and Pittman, 2001).…”
Section: Discussionsupporting
confidence: 93%
“…6C). Consistent with findings in the SON (Azdad et al, 2003), we also observed an inhibition of IPSCs by the D 4 receptor agonist PD168077 (30 M; 69.3 Ϯ 11.5% depression; n ϭ 7; data not shown) but not by quinpirole, an agonist for the D 2 -like receptor family (90 M; 5.2 Ϯ 9.3% depression; n ϭ 5; data not shown).…”
Section: Dopamine Reversibly Decreases P Rsupporting
confidence: 88%
See 2 more Smart Citations
“…KARs are positively coupled to GABA release in the SON Earlier studies described the action of various presynaptic receptors on GABA terminals in the SON (Kabashima et al, 1997;Schrader and Tasker, 1997;Wang et al, 1998;Oliet and Poulain, 1999;Li et al, 2001;Stern and Ludwig, 2001;Azdad et al, 2003) but no particular attention was paid to that of KARs. For this purpose, we performed recordings on miniature IPSCs (mIPSCs) in slices from animals under basal, nonstimulated conditions of neurosecretion, i.e., normally hydrated male and virgin female rats.…”
Section: Resultsmentioning
confidence: 99%